Exploring the usefulness and feasibility of software requirements for social media use in emergency management. (January 2020) - Hiltz, S. Roxanne; Hughes, Amanda Lee; Imran, Muhammad; Plotnick, Linda; Power, Robert; Turoff, Murray
Abstract: Social Media (SM) contain a wealth of information that could improve the situational awareness of Emergency Managers during a crisis, but many barriers stand in the way. These include information overload, making it impossible to deal with the flood of raw posts, and lack of trust in unverified crowdsourced data. The purpose of this project is to build a communications bridge between emergency responders and technologists who can provide the advances needed to realize social media's full potential. We employed a two round Delphi study survey design, which is a technique for exploring and developing consensus among a group of experts around a particular topic. Participants included emergency managers, researchers, and technologists with experience in software to support the use of SM in crisis response, from many countries. The study topics are described, and results are presented for both Round 1 (N = 36) and Round 2 (N = 29) of the study, including a ranked list of the top 16 useful features. The top four features include: viewing SM data as classified by geographic location with map-based display; viewing SM data as generated by categories of users; dynamically extracting emerging information; and automatically processing SM images to identify relevant ones.